2016
DOI: 10.1186/s12950-016-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of peripheral B cell populations during Mycobacterium tuberculosis infection and disease

Abstract: BackgroundMycobacterium tuberculosis (Mtb) remains an unresolved threat resulting in great annual loss of life. The role of B cells during the protective immunity to Mtb is still unclear. B cells have been described as effector cells in addition to their role as antibody producing cells during disease.Here we aim to identify and characterize the frequency of peripheral B-cell subpopulations during active Tuberculosis and over treatment response. Analysis were done for both class switched (CS) and non-class swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The details of B‐cell and IgM antibody dynamics during TB, anti‐TB therapy and vaccination in humans remain unclear. A recent study found distinct B‐cell subpopulations in peripheral blood during active TB disease and other lung disease conditions . Although Plessis et al .…”
Section: Discussionmentioning
confidence: 99%
“…The details of B‐cell and IgM antibody dynamics during TB, anti‐TB therapy and vaccination in humans remain unclear. A recent study found distinct B‐cell subpopulations in peripheral blood during active TB disease and other lung disease conditions . Although Plessis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Current research findings have signified the importance of B-cells during M.tb infection, in which absence or impaired function of this immune cell type has been associated with poor disease prognosis (Achkar et al, 2015; Bénard et al, 2018; Du Plessis et al, 2016a, 2016b; Rao et al, 2015). For decades, the primary function of B-cells was considered to be antibody secretion, forming part of the adaptive humoral response (Abbas et al, 2014; Zabriskie, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study found that LLPCs are important contributors of cytokine production during LTBI (115). MBCs and LLPCs generate the AMIR through the production of IL-21 and the subsequent induction of a B cell maturation loop involving the formation of PCs (108,116). Preliminary evidence suggests that this response is crucial for controlling Mtb infection (108,116).…”
Section: B Cells In Memory Responses Against Mtbmentioning
confidence: 98%
“…Some preliminary findings suggest that the proportion of distinct MBC subsets may predict the clinical status of Mtbinfected patients (Figure 2), arguing in favor of a role of B cell memory in TB (108,(115)(116)(117)(118)(119). For instance, MBC, plasmablasts, and PCs subsets are significantly enriched in the circulation of patients with active TB, and their proportions diminish after the conclusion of anti-TB treatment, suggesting that these B cells subsets undergo a contraction phase after antigen clearance (119).…”
Section: B Cells In Memory Responses Against Mtbmentioning
confidence: 99%
See 1 more Smart Citation